URANIUM-LEAD AGE OF GRANULITES OF THE KURUL'TA COMPLEX, ALDAN SHIELD - Bibikova Ye.V.; Gracheva T.V.; Drugova G.M.; Makarov V.A.; Morozova I.M. (My University, 1989)
The question of the age of oldest rocks on the Aldan shield is keenly debated. We analyze the results of our uranium-lead isotope dating of accessory zircons from mafic rocks of the Kurul'ta complex. This Early Archean complex is part of the Olekma fold system and is regarded as one of the oldest in the region, containing supracrustal rocks. It forms separate blocks, arranged along the periphery of this fold system. We have been able for the first time to date the Early Archean granitization of rocks of the Kurul'ta complex, which occurred 3460 ± 16 m.y. ago under conditions of the granulite metamorphic facies. Therefore, the Kurul'ta complex of the Aldan shield can quite rightly be regarded as one of the oldest.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей